ASSESSMENT OF STUDENTS 'PHYSICAL HEALTH AND GROUPING INTO GROUPS ACCORDING TO THEIR MEDICAL PHYSICAL CONDITION - Sodiqov Sardorbek Azamjonovich; M.T. Botaboev (Galaxy International Interdisciplinary Research Journal, 2021)
The use of new pedagogical technologies in the process of physical and fitness activities of students, research, approach to the process of training, taking into account the personal interests and physical abilities of students, their formation in physical activity, guidance and advice on student health I think it needs serious attention. In this short article, we will try to assess the health of students and conduct research based on their medical condition in groups.